IgE antibody repertoire in nasal secretions of children and adults with seasonal allergic rhinitis: A molecular analysis. Issue 3 (22nd January 2020) - Castelli, Sveva; Arasi, Stefania; Tripodi, Salvatore; Villalta, Danilo; Martelli, Paola; Conte, Mariaelisabetta; Panetta, Valentina; Simonelli, Ilaria; Rohrbach, Alexander; Di Fraia, Marco; Sfika, Ifigenia; Villella, Valeria; et al.
Abstract: Background: There is growing interest both in testing IgE in nasal secretions (NS) and in molecular diagnosis of seasonal allergic rhinitis (SAR). Yet, the reliability of nasal IgE detection with the newest molecular assays has never been assessed in a large cohort of pollen allergic patients. Objective: To investigate with microarray technology and compare the repertoires of specific IgE (sIgE) antibodies in NS and sera of a large population of children and adults with SAR. Methods: Nasal secretions were collected with an absorbent device (Merocel 2000 ®, Medtronic) and a minimal dilution procedure from 90 children and 71 adults with SAR. Total IgE (tIgE) (ImmunoCAP, Thermo Fisher Scientific (TFS)) and sIgE antibodies against 112 allergen molecules (ISAC‐112, TFS) were measured in NS and serum. Results: Nasal sIgE was detectable in 68.3% of the patients. The detected nasal sIgE antibodies recognized airborne (88%), vegetable (10%), and animal food or other (<1%) allergen molecules. The prevalence and average levels of sIgE in NS and serum were highly interrelated at population level. A positive nasal sIgE antibody to a given molecule predicted the detection of the same antibody in the patient's serum with a specificity of 99.7% and a sensitivity of 40%. Conclusions: The concentration of sIgE is much lower in nasal secretions than in the serum. sIgE assays with very high analytical sensitivity and sampling methods with minimal dilution will be therefore needed to validate nasal secretions as alternative to serum in testing the sIgE repertoire. Abstract :